Maternal depressive symptoms and children's academic performance: sex differences in the mediating role of school experiences - Ahun, Marilyn N.; Psychogiou, Lamprini; Guay, Frédéric; Boivin, Michel; Tremblay, Richard E.; Côté, Sylvana M. (Psychological medicine)
Background Maternal depressive symptoms (MDSs) are negatively associated with children's academic performance, with stronger effects sometimes reported in boys. However, few studies have tested the mechanisms of this association. We examined the mediating role of school engagement and peer victimization in this association and tested for sex differences. Methods Participants were 1173 families from a population-based longitudinal Canadian study. MDSs were self-reported annually using the Centre for Epidemiologic Studies Depression Scale (child's age: 5 months to 5 years). Data on mediators (peer victimization, cognitive, behavioral, and emotional school engagement) were reported annually from ages 6-10 by multiple informants including children, parents, and teachers using items from validated scales. Mathematics, reading, and writing exam scores at age 12 were obtained from standardized exams administered by Quebec's Ministry of Education and Teaching. Structural equation modeling was used to test mediation by school experiences in boys and girls. Results Exposure to MDSs was negatively associated with mathematics, reading, and writing scores in girls and with mathematics only in boys. Cognitive and behavioral engagement significantly mediated the association between MDSs and mathematics, reading, and writing scores in girls. There were no significant mediators for boys. Conclusions Prevention and intervention strategies aiming to improve school engagement might be beneficial for daughters of mothers experiencing depressive symptoms. Further research is needed to replicate these findings and to identify the mechanisms explaining this association in boys.